Analysis of the effects of closing process of guide vanes on the water hammer pressure value of the Houya hydropower station, Laos - Nguyen ,Thi Nho (Trường Đại học Thuỷ lợi, 2022)
This paper presents the numerical simulation results to analyze the effects of the closing process of guide vanes on the water hammer pressure values and fluctuations in the surge tank for the Houya Hydropower Station, Laos. The three processes of opening and closing the unit at the respective durations of 8.2; 8.04 and 7.18s show that the water hammer pressure value increases 60%, 58.2% and 58% respectively. This result shows that it is not possible to have this limited overpressure in 8 seconds closing time with any torque of the unit of GD2. For the selected speed of the machine, it is recommended that the results are satisfactory with 30 seconds closing time. It is also recommended to use the results of vertical pressure distribution along the energy line in case 3 to design the structure of the box channel and steel pipe, ensure no breakage for the box channel and safety for steel pipe.